2018
DOI: 10.1016/j.fcr.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Testing pearl millet and cowpea intercropping systems under high temperatures

Abstract: With the potential threat of more frequent climate extremes putting semi-arid crop production in jeopardy, there is a need to establish more climate resilient cropping practices. Intercropping is often practiced by farmers in semi-arid regions and is perceived as a risk reducing practice. However, there is little knowledge of how and to what extent it can be a viable option under future conditions. As testing a complex adaptation strategy in controlled environments is difficult, conducting field experiments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
4
19
0
3
Order By: Relevance
“…The differences in pLER between CA and CT when maize was intercropped with cowpea could be explained in terms of efficient utilisation of water resources in intercrop systems. Similar results have been reported by (Chimonyo et al 2018;Nelson et al 2018) who demonstrated reduced competition for water resources between cereals and cowpea grown in intercrops. Pigeon pea shows slow growth in the initial stages of plant growth and takes over after maize has matured, thus offering little competition to maize (Sakala et al 2000).…”
Section: Maize Productivitysupporting
confidence: 89%
“…The differences in pLER between CA and CT when maize was intercropped with cowpea could be explained in terms of efficient utilisation of water resources in intercrop systems. Similar results have been reported by (Chimonyo et al 2018;Nelson et al 2018) who demonstrated reduced competition for water resources between cereals and cowpea grown in intercrops. Pigeon pea shows slow growth in the initial stages of plant growth and takes over after maize has matured, thus offering little competition to maize (Sakala et al 2000).…”
Section: Maize Productivitysupporting
confidence: 89%
“…The high adoption rate of these practices can be attributed to the fact that crop yield increases with the adoption of intercropping, micro dosing and FMNR practices which in long run can better contribute to food security [6,34,35]. In semi-arid crop production where there is a potential treat of more frequent climate extremes, intercropping is an important crop production strategy for smallholder farmers for productivity improvements per unit of land [36]. Previous studies reveal that intercrop systems provide benefits such as complementary use of resource niches in term of the different rooting behavior of crops [37] and better system protection again pests and diseases [38].…”
Section: Awareness and Adoption Of Csa Practices And Technologies: Admentioning
confidence: 99%
“…However, it must be taken into consideration that competition between plants for natural resources such as water, light and nutrients in an intercropped system is inevitable, and this leads to distinct yields between monocultures and intercropping (Sadeghpour et al, 2013). Nelson et al (2018) found that intercropping with cowpea significantly decreased millet yield in a semi-arid region of India; however, millet was tolerant to the region's high temperatures and water restriction in treatments with poor irrigation.…”
Section: Intercroppingmentioning
confidence: 99%
“…It is a plant that possesses the Crassulacean Acid Metabolism (CAM), with high water storage capacity and high efficiency in its utilization, besides being rich in energy and minerals (Scalisi et al, 2016). Despite the forage cactus present several qualities, it is a culture poor in fiber (Ben Salem and Smith, 2008), this characteristic is observed among other cultures as in the millet (Pennisetum glaucum) which, in turn, also appears as a good alternative to boost the production of forage, since it is a species of metabolism C4, averagely tolerable to salinity, as well as the hydric stress and to the high temperatures (Nelson et al, 2018), common features in the arid and semiarid regions. It also possesses good biomass production and nutritive value (Santos et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%